1998
DOI: 10.1037/0022-3514.74.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Parents' influence on children's achievement-related perceptions.

Abstract: Two aspects of the relation between parents' perceptions of their children and children's self- and task perceptions in math and English were investigated: (a) the mediating role of parents' perceptions between grades and adolescents' self-perceptions and (b) the gendered nature of parents' perceptions. Data for this study are part of a longitudinal investigation (the Michigan Study of Adolescent Life Transitions). Data from 914 sixth-grade adolescents and their parents are used in this article. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
383
6
26

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 429 publications
(438 citation statements)
references
References 32 publications
23
383
6
26
Order By: Relevance
“…The findings indicate a strong positive link between the two variables (Bandura, Barbaranelli, Caprara, & Pastorelli, 1996;De Civita et al, 2004;Frome & Eccles, 1998;Okagaki & Sternberg, 1993), and this relationship seems robust across cultures and age groups (Aston & McLanahan, 1991;De Civita, Pagani, Vitaro, & Tremblay, 2004;Halle, Kurtz-Costes, & Mahoney, 1997;Neuenschwander, Vida, Garrett, & Eccles, 2007). In fact, among the various specific components of parental involvement, parental aspiration yielded the largest effect size in relation to academic performance, as shown by meta-analytic findings (Fan & Chen, 2001;Jeynes, 2005Jeynes, , 2007.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The findings indicate a strong positive link between the two variables (Bandura, Barbaranelli, Caprara, & Pastorelli, 1996;De Civita et al, 2004;Frome & Eccles, 1998;Okagaki & Sternberg, 1993), and this relationship seems robust across cultures and age groups (Aston & McLanahan, 1991;De Civita, Pagani, Vitaro, & Tremblay, 2004;Halle, Kurtz-Costes, & Mahoney, 1997;Neuenschwander, Vida, Garrett, & Eccles, 2007). In fact, among the various specific components of parental involvement, parental aspiration yielded the largest effect size in relation to academic performance, as shown by meta-analytic findings (Fan & Chen, 2001;Jeynes, 2005Jeynes, , 2007.…”
mentioning
confidence: 88%
“…First, many of the previous studies tested the relation between parental aspiration and student's academic achievement using cross-sectional or prospective designs (e.g., Bandura et al, 1996;Davis-Kean, 2005;De Civita et al, 2004;Frome & Eccles, 1998;Okagaki & Sternberg, 1993;Pearce, 2006). Such designs leave the temporal order of aspiration and achievement unclear.…”
Section: Temporal Ordering and Possible Reciprocal Effectsmentioning
confidence: 99%
“…Early research surmised that boys' putatively superior spatial skills manifest themselves in a gender math gap and produce disparate consequences across educational trajectories Stanley 1981, 1982). However, more recent scholarship has highlighted the role of family factors in mathematical aptitude (Casad et al 2015;Entwisle et al 1994;Frome and Eccles 1998), an influence that had been noted in some early research as well (Benbow and Stanley 1980;Block 1983). Parents' gender ideologies influence their children's self-confidence with respect to math (Muller 1998), and parents with traditional gender attitudes tend to have daughters with diminished mathematical self-efficacy (Frome and Eccles 1998;Jacobs and Eccles 1992;Jacobs 1991;Parsons et al 1982;Schafer and Gray 1981).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Parents' gender ideologies influence their children's self-confidence with respect to math (Muller 1998), and parents with traditional gender attitudes tend to have daughters with diminished mathematical self-efficacy (Frome and Eccles 1998;Jacobs and Eccles 1992;Jacobs 1991;Parsons et al 1982;Schafer and Gray 1981). Parents with lower mathematical expectations for their daughters tend to have daughters with less ambition in math (Casad et al 2015;Frome and Eccles 1998;Parsons et al 1982). Moreover, because parents of daughters may underestimate the importance of math skills for long-term professional development, they often (1) provide less positive verbal reinforcement related to math; (2) rationalize their daughters' sub-par math performance; and (3) offer less homework assistance (Muller 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Parents may convey beliefs about their child's competencies through the messages they give regarding the difficulty and importance of achievement tasks (Eccles, Adler and Kaczala 1982), and longitudinal studies have demonstrated parents exert a powerful influence on children's subsequent perceptions of competence (e.g. Frome andEccles 1998, Jacobs andEccles 1992). Students' perceptions of competence have been found to become more highly correlated with teacher ratings of student ability in the fifth and sixth grades (Harter 1982).…”
Section: Sources Of Students' Academic Perceptionsmentioning
confidence: 99%